Outcome of patients with intermittent stab peritoneal dialysis: a single centre experience - Wan Ali, Wan Ahmad Syahril Rozli; Seman, Mohd Ramli; Draman, Che Rosle (2014)
Background: Intermittent stab peritoneal dialysis (IPD) is still practiced in our centre as a modality used in patients refusing long term renal replacement therapy (RRT); and in elderly patients with significant comorbidities, who are unable to undergo RRT for various reasons. Objective: To analyze the characteristics and outcomes of stab peritoneal dialysis as a modality in acute dialysis, and prior to definitive renal replacement therapy. Methods: In this cross sectional study, fourty one episodes of stab peritoneal dialysis, involving thirty five patients undergoing stab peritoneal dialysis in Hospital Tg. Ampuan Afzan from December 2012 until June 2013 were recruited. The sociodemographic, laboratory investigations and other relevant profiles in these patients were assessed. Results: The majority of the patients were males (61.0 %). The mean age was 50.8 + 15.1 years old (95% CI 46.1 - 55.6). Diabetes mellitus was the commonest comorbid (75.6 %), followed by Hypertension (63.4%) and ischaemic heart disease (17.1%). Eighteen (43.9%) of the procedure was done in Nephrology ward, followed by seventeen (41.5%) in high dependency ward. Fourteen patients (40.0%) already underwent stab peritoneal dialysis more than once due to refusal for long RRT, and presented acutely in the ward. Six (14.6%) of the patients from the high dependency unit were intubated during the procedure, and all of them required high dose inotropic support. The mean systolic blood pressure was 144.3 + 4.1 mmHg (95% CI 136.0-152.6), and diastolic blood pressure was 79.6 + 2.5 mmHg (95% CI 74.6-84.5). Laboratory investigations prior to procedure showed mean Potassium 4.87 + 0.83 mmol/L, Urea pre 42.2 + 12.0 mmol/L, Creatinine pre 1054.9 + 564.0 mmol/L, Bicarbonate 16.6 + 4.4 mmol/L, Haemoglobin 9.1 + 2.6 g/dL, Albumin 29.4 + 7.2 g/L. The post procedure mean Urea was 31.4 + 10.5 mmol/L, Creatinine 854.7 + 532.1 mmol/L, and Potassium 3.9 + 0.5 mmol/L. The mean ultrafiltrate was 4356 + 3747 mililitres ( 95% CI 2601 – 6110 ). Nine (22.0%) patients developed poor flow and needs to be adjusted. Three (8.6%) patients need to be converted to Haemodialysis in view of very poor solute clearance. Only two (4.9%) patients developed minor bleeding, and one (2.8%) developed peritonitis. Conclusion: The IPD population consisted of middle-aged patients, majority were males, and diabetics. Multiple stab peritoneal dialysis has been done in some patients, with minimal complications. The main concern was the high ultrafiltration rates and low and slow solute clearance rates in patients undergoing IPD. References : - Intermittent peritoneal dialysis (IPD): an old but still effective modality for severely disabled ESRD patients. Fourtounas et.al. Nephrol Dial Transplant. 2009 Oct;24(10):3215-8